Revisión Del Uso De Plástico Reciclado En La Construcción De Viviendas - Muñoz Sepúlveda, Lizbeth Johana (Universidad Antonio Nariño, 2025)
The purpose of this study is to evaluate the technical, economic, and environmental feasibility of using recycled plastic in construction through a literature review that compares its effectiveness with traditional methods. The methodology is descriptive and analytical, developed in several stages, including: Identification of Technical Characteristics, Review of Case Studies, Economic and Environmental Comparison, and Social Impact Assessment. The results demonstrate the effectiveness of recycled plastics, highlighting Polycarbonate (PC) for its high compressive strength (60 to 70 MPa) and impact resistance (15 to 20 kJ/m²), properties relevant to the durability of structures.